Awareness and attitudes of Saudi parents toward otitis media in children - Alsuhaibani, Mohammed (J Family Med Prim Care, 2020)
BACKGROUND: An ear infection is a common health problem in children. Parents’ awareness about otitis media (OM) among children, varies across the world. We aimed to explore parents’ knowledge, attitude, and practices toward OM among their children. METHODS: A quantitative cross-sectional study was done from May 1, 2020 to June 30, 2020, in Qassim, Saudi Arabia. RESULTS: This study comprised 703 participants; Mothers comprised the majority (77.1%), 43.2% of the participants were aged between 31 and 40 years of age, and 73% of them had Bachelor's degrees or diplomas. More than half of the participants had suboptimal knowledge of OM. Although the result showed that 56% of them had positive attitudes, 86.6% did not view vaccination as a prevention measure of acute OM (AOM). Besides, 81.8% of parents were willing to follow the watchful waiting approach, in case their child had OM. CONCLUSION: Most of the parents in the Qassim region have inadequate knowledge regarding OM among children. Based on our result findings, we recommend further education programs to enhance the knowledge regarding OM and AOM, among the Qassim population, Saudi Arabia including family members of patients and the healthcare workers.